Connected education and the co-construction of knowledge in a joint course for law and interpreting students - Kadric, Mira; Rennert, Sylvi; Mikic, Dalibor (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article raises questions of education sociology with a focus on one of its core concepts: connectedness. It relates the dimensions of the connected curriculum to research on didactic approaches, showing how methods of connected learning and the co-construction of knowledge can be applied at different levels to enable students to gain subject-related, methodological and transdisciplinary communicative competence in addition to building relationships and cooperation among them across fields of study. These dimensions are presented using the example of the course “Questioning techniques from the perspective of criminology and interpreting”. During this course, students of law and interpreting had the opportunity to acquire both core theoretical knowledge of and practical experience in questioning techniques. This they did through role playing the questioning of defendants and witnesses that typically occurs in a courtroom from the perspective of both criminology and interpreting. The evaluation and feedback showed that the law and the interpreting students appreciated the way the course made them aware of issues in both their own and the other field, helped them to connect academic learning to professional competences and gave them insights into interprofessional cooperation in interpreted legal settings.